2016
DOI: 10.1038/srep25713
|View full text |Cite
|
Sign up to set email alerts
|

Blast shockwaves propagate Ca2+ activity via purinergic astrocyte networks in human central nervous system cells

Abstract: In a recent study of the pathophysiology of mild, blast-induced traumatic brain injury (bTBI) the exposure of dissociated, central nervous system (CNS) cells to simulated blast resulted in propagating waves of elevated intracellular Ca2+. Here we show, in dissociated human CNS cultures, that these calcium waves primarily propagate through astrocyte-dependent, purinergic signaling pathways that are blocked by P2 antagonists. Human, compared to rat, astrocytes had an increased calcium response and prolonged calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…36 Although the type of insult is different from ours, a similar mechanism might be involved. This is because overpressure of a shock wave can increase intracellular calcium (Ca 2þ ), 38,39 resulting in activation of endothelial nitric oxide synthase (NOS) and hence an increase in nitric oxide (NO). 40 Meanwhile, an intracellular increase in Ca 2þ can stimulate the generation of reactive oxygen species (ROS) in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…36 Although the type of insult is different from ours, a similar mechanism might be involved. This is because overpressure of a shock wave can increase intracellular calcium (Ca 2þ ), 38,39 resulting in activation of endothelial nitric oxide synthase (NOS) and hence an increase in nitric oxide (NO). 40 Meanwhile, an intracellular increase in Ca 2þ can stimulate the generation of reactive oxygen species (ROS) in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the reported values in these publications are similar to those obtained here. Our new findings suggest that a diffusible purinergic signal released by astrocytes themselves activates astroglial P2Y 1 R (i.e., astrocyte-to-astrocyte signaling) and upregulates the incidence of STs, which is supported by several evidences: (i) TTX-insensitive neurotransmitter release is associated with FTs confined to microdomains in astrocytic processes and not to somatic Ca 2+ oscillations (Di Castro et al, 2011 ; Álvarez-Ferradas et al, 2015 ); (ii) ATP is released by astrocytes as a mechanism for paracrine signaling in several neuropathologies, being P2YR-mediated signaling one of the main pathways for astrocyte-to-astrocyte communication in pathological conditions (Anderson et al, 2004 ; Iwabuchi and Kawahara, 2011 ; Pascual et al, 2012 ; Orellana et al, 2013 ; Delekate et al, 2014 ); and (iii) astrocytes generate Ca 2+ transients as a consequence of P2YR activation (Bowser and Khakh, 2007 ; Torres et al, 2012 ), which is also observed in pathological conditions, including epilepsy (Delekate et al, 2014 ; Álvarez-Ferradas et al, 2015 ; Ravin et al, 2016 ; Reichenbach et al, 2018 ). In addition, it has been shown that P2Y 1 R induces large and long-lasting astrocytic Ca 2+ transients that do not require action potentials for their generation (Gallagher and Salter, 2003 ; Shigetomi et al, 2018 ), which is consistent with our previous findings (Álvarez-Ferradas et al, 2015 ) and with the decrease in the frequency and percentage of STs associated with P2Y 1 R blockade in the epileptic hippocampus above described (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blast shock waves are generated by explosives. As a model of blast injury, the intracellular Ca 2+ increase evoked in astrocytes by blast shock waves was investigated 45,46 . The peak pressure of the blast shock waves was relatively comparable: around 1 MPa for blast shock waves and typically 3.8 MPa for shock waves in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%